Keputusan Investasi Keluarga Ditinjau dari Perilaku Herding dan Risk Tolerance serta Faktor Demografi: Studi di Kota Tasikmalaya - Yusnita, Rita Tri (IMAGE : Jurnal Riset Manajemen, 2021)
According to behavioral finance theory, a person's investment decisions can involve aspects or elements of behavior, so that they are influenced by irrational attitudes. This study aims to determine individual behavior in making family investment decisions in terms of herding behavior and risk tolerance as well as demographic factors in the community in the city of Tasikmalaya. Primary data was taken by distributing questionnaires with snowball sampling technique and collected as many as 247 samples. Data were analyzed using crosstabs analysis and multiple regression analysis. The results of the descriptive analysis showed that the people of the city of Tasikmalaya are more likely to choose to invest in moderate risk assets and low risk assets, with a fairly low level of herding behavior and a fairly low level of risk tolerance. The results of the crosstabs analysis showed that there was no significant difference in determining the choice of the type of family investment, between women and men in the Tasikmalaya city community. However, the results of the analysis of other demographic factors, namely marital status, income, and age, there are significant differences in determining the choice of the type of family investment. The results of the multiple regression test showed that herding behavior and risk tolerance, simultaneously, had a significant effect on family investment decisions in the community in the city of Tasikmalaya. The results also showed that partially herding behavior had no significant effect on investment decisions in the community in the city of Tasikmalaya, but risk tolerance partially had a significant effect on investment decisions in the community in the city of Tasikmalaya..Â